Sustainable Economic Growth And Creative Destruction In The Economy - Piotr WALAG; Dominika KULIŃSKA (Communications of International Proceedings, 2021)
Sustainable economic growth is defined as continuous economic growth with full employment, resistant to economic shocks and crises, as well as the demand shocks they carry. Sustainable economic growth requires the emergence of new industries which, achieving high growth dynamics, will "compensate" the inevitable slowdown in the spread of inventiveness and innovation in old branches. Hence, sustainable economic growth, as argued by JA Schumpeter (1942), is brought about by creative economic destruction, which, as noted by L. Thurow (1980), requires more than once painful but necessary cuts, divestments and reinvestments in order for new (technologies) industries to emerge. replacing the old ones. Therefore, the high growth rate of the economy as a whole must be accompanied by significant shifts in relative importance between industries as old ones collapse and new ones arise. Lack of allocation of production factors or allocation that is not economically effective (efficiency in the sense of Pareto) is a brake on further (sustainable) growth, and therefore economic development). The issue of structural changes from the point of shaping, and at the same time achieving sustainable, sustainable economic growth through the efficiency of managing production factors (effective allocation) is a key area of ​​research on changes in the structure of the economy as such. The aim of this article is to investigate to what extent the level of innovation in the industrial sector determined the processes of changes in the structure of the Polish economy in 1995–2018, and whether the lack of innovation in the processing industry could be the main cause of the average growth trap in the Polish economy in the analyzed period. It is also hypothesized that the level of innovation in the industrial sector is the main criterion for the desired (effective) economic conditions necessary to achieve sustainable long-term economic growth.  To achieve the goal and verify the hypothesis, a statistical analysis of the prevailing factors, the key determinants of changes in the structure of the economy in terms of employment and production, was used. A regression analysis of estimated and calibrated models of changes in the share in employment and total production of the processing industry was used, using the developed meso-economic and macroeconomic indicators (based on studies, as well as danGUS and WTO, as well as OECD and EUROSTAT). The research carried out as part of this article on changes in the structure of the Polish economy has shown that the constantly growing demand / demand, and above all GDP per capita, was most determined by the change in the production volume of the processing industry, being the most influencing explanatory variable (dominant factor) of the changes (increase and decrease) of its share in total production for the entire analyzed period, which clearly showed that it is the strongest / main determinant of the share of industry in total employment. However, as a result, on the other hand, a very low level of innovation in the processing industry sector caused (determined) a decline in its share in total employment, being the main determinant (key / predominant) cause of jobless economic growth, which would suggest (create / cause) the phenomenon of the average trap growth. This was the greatest barrier to achieving sustainable, long-term economic growth. Moreover, the analysis of the prevailing factors (main determinants) of changes in the structure of the Polish economy in the analyzed (analyzed) period showed the phenomenon of the dualism of deindustrialization processes (economic evolution as such) occurring in this economy (Poland).
Keywords: Sustainable Economic Growth; Creative Destruction; Effective Allocation Of Production Factors; Economic Evolution; Innovations; Divestments And Reinvestments.